Occurrence of marine fungi from the Straits of Malacca, Malaysia, with first record of Mauritiana rhizhoporae - Zainuddin, Nazura; Sharuddin, Siti Sarah; Alias, Siti Aisyah (Malaysian Journal of Science, 2008)
The inventory of marine fungi along the Straits of Malacca was carried out in July, 2004 and December, 2007. Three locations were investigated for their marine fungal diversity: Lalang Island, Jarak Island and Rumbia Island. Samples collected from these islands were submerged wood and driftwood entrapped in between rocks, embedded in sand and washed ashore along the coastal areas. A total of 51 species of marine fungi were recorded from 274 samples collected and their frequency of occurrence is discussed. Mauritiana rhizophorae is reported as the first record in Malaysia. Inventori kulat marin di sepanjang Selat Melaka telah dijalankan pada Julai, 2004 dan Disember, 2007. Tiga lokasi telah dijalankan bagi kajian kepelbagaian kulat laut: Pulau Lalang, Pulau Jarak dan Pulau Rumbia. Sampel-sampel yang dikutip daripada pulau-pulau ini terdiri daripada kayukayu yang terendam dan kayu terampai yang terperangkap di antara batu-batu besar, terbenam di dalam pasir dan yang terampai di sepanjang pesisiran pantai. Sejumlah 51 spesis kulat laut telah direkodkan daripada 274 sampel-sampel yang dikutip dan kekerapan kehadirannya dibincangkan.